The use of imaging tests to obtain optimal margins in breast surgery - Ostańska, Elżbieta; Bartusik-Aebisher, Dorota; Gustalik, Joanna; Aebisher, David; Galiniak, Sabina; Kaznowska, Ewa (European Journal of Clinical and Experimental Medicine, 2019)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. The proper negative margins (R0) breadth in the breast - conserving surgery for invasive breast cancer (IBC) and ductal carcinoma in situ (DCIS) is very important. The presence positive surgical margins (R1) is associated with the necessity of reoperation. It delays the adjuvant therapy and psychologically burdens the patient. The re-operation increases the costs of treatment. The introduction of mammography (MMG) increased detection of DCIS by 20%. With the increase in malignancy, cancer detection decreases in MMG, inversely in MRI groving. Effective preoperative and intraoperative diagnosis aims to reduce the number of R1 resections. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The size of the tumor next to its biology, determines the clinical course of the tumor. The accurate analysis of imaging tests is important. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. This analysis was performed using a systematic literature search. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Adequate surgical margins in breast cancer surgery for breast cancer have been reviewed. It is important to know if the cancer is multifocal and what the extent of the tumor is. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The adequacy of margins is important for adjusting the volume of excision. It is avoiding unnecessary resection of healthy breast tissue. It is essential for a good cosmetic result and the local recurrence rate. The combination of breast MRI with conventional breast imaging resulted in the lover rate of the R1 resectios and the lower rate of the re-operation.